2003
DOI: 10.1248/cpb.51.1006
|View full text |Cite
|
Sign up to set email alerts
|

Insulinomimetic Zinc(II) Complexes with Natural Products: In Vitro Evaluation and Blood Glucose Lowering Effect in KK-Ay Mice with Type 2 Diabetes Mellitus

Abstract: In vitro insulinomimetic activities of Zn(II) complexes with three natural products, betaine, L-lactic acid, and D-(-)-quinic acid (qui), were found in rat adipocytes treated with epinephrine in terms of the inhibition of free fatty acid release. Based on the results, the blood glucose lowering effect in KK-A(y) mice with type 2 diabetes mellitus was observed by daily i.p. injections of a monomeric zinc(II) complex, Zn(qui)(2), for 13 d.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
1

Year Published

2004
2004
2009
2009

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 25 publications
2
17
1
Order By: Relevance
“…It has been suggested that an additional supplement of zinc may be useful in diabetics. Similar protective effects of zinc on blood glucose levels have been emphasized in other studies [6,[25][26][27].…”
Section: Discussionsupporting
confidence: 82%
“…It has been suggested that an additional supplement of zinc may be useful in diabetics. Similar protective effects of zinc on blood glucose levels have been emphasized in other studies [6,[25][26][27].…”
Section: Discussionsupporting
confidence: 82%
“…Daily intraperitoneal injections of these Zn(II) complexes for 14 days attenuated hyperglycemia, hyperinsulinemia and hyperlipidemia, and improved oral glucose tolerance and HbA1c values in KK-A y mice (Type 2 diabetes model) without negative effects on indices of renal and hepatic function (Yoshikawa et al 2001Kojima et al 2003). Similar results have been reported in GK rats (non-obese Type 2 diabetes model) given Zn(II) complexes intraperitoneally or by oral administration for 30-45 days (Fugono et al 2002).…”
Section: Zn and Type 2 Diabetes Modelssupporting
confidence: 72%
“…In addition, Zn salts have several disadvantages such as low absorption and short turnover. Zn complexes with superior properties that will overcome these limitations are being developed (Kojima et al 2003;Song et al 2003;Yoshikawa et al 2004). A promising future for Zn supplementation will warrant further studies.…”
Section: Resultsmentioning
confidence: 99%